Economic evaluation on pentavalent vaccine versus hexavalent vaccine in childhood immunization programs: A systematic review - Fadhila Aulia Dila; Raodiatul Jumiati; Fitri Fitri; Eka Abelian Putri Kelana; Sulistyaningsih Sulistyaningsih; Putri Listiani (Journal of Health Technology Assessment in Midwifery, 2026)
Background: The childhood immunisation programme is a key pillar in the prevention of infectious diseases. The hexavalent vaccine, which combines six antigens (DTPa-HepB-IPV-Hib) in a single formulation, offers a practical alternative to pentavalent vaccines used in combination with separate hepatitis B and polio vaccines. This study aims to evaluate and compare the economic aspects of pentavalent and hexavalent vaccines across various forms of economic evaluation to support the sustainability of childhood immunisation programmes.Method: This systematic review was conducted following PRISMA 2020 guidelines using the PICO framework. Articles were retrieved from PubMed, ScienceDirect, and EBSCO databases using MeSH-based keywords. Inclusion criteria covered articles published within the last five years comparing hexavalent and pentavalent vaccines in childhood immunisation programmes for children aged 0–2 years. Study quality was assessed using Drummond's 10-item checklist.Results: Six studies from Colombia, Peru, Argentina, Chile, South Korea, and China were analysed. All studies assumed comparable clinical efficacy between vaccines and applied the cost-minimisation analysis (CMA) approach. From both health system and societal perspectives, the hexavalent vaccine consistently demonstrated lower total costs per fully immunised child (FIC). Key efficiency drivers included a reduction in injections, fewer health facility visits, reduced adverse events, and improved healthcare worker efficiency. Results remained robust across sensitivity analyses conducted in all models.Conclusion: Although more expensive per dose, the hexavalent vaccine proved more efficient and cost-effective in childhood immunisation programmes, especially in settings with logistical constraints. These findings support the integration of the hexavalent vaccine into national immunisation policies.